Evaluasi Dampak Kredit Mikro Terhadap Kesejahteraan Rumah Tangga di Indonesia: Analisa Data Panel - Setyari, Ni Putu Wiwin (Jurnal Ekonomi Kuantitatif Terapan; 2012: Vol. 5, No. 2, Agustus 2012 (pp. 79-150), 2012)
The objective of the research was to evaluate the impact of micro-cridit impact towartd houshold prosperity in Indonesia. Nowadays, many micro-finance researches are focused on programes based on the Bangladesh Grameen Bank programes and its innovation, specialy credit for women, meanwhile the empirical evidence concerning the impact and nature of the credit has not been well presented. The acknowledgment of the credit benefits by Indonesian Government was indicated by launch the microfinance years in 2005. The data, which used in the research, is the IFLS 3 and IFLS 4. The fixed effect methode revealed that micro credit have positive and significant impact toward household prosperity in Indonesia. The positive impact was indicated by the increasing amount of percapita expenditure and labor supply from the treated household. The research also found that childrend education level has not significant effect and indicated adverse effect instead.
Keywords: impact evaluation , micro-credit , household prosperity , panel data analysis